The effects of innovation on channels on distribution - Gattorna, J. L. (Cranfield University, 1977)
There exists a certain wisdom in management which accepts that there will always be problems which by their very nature are insoluble; nevertheless many remain which, due to the application of particular management skills, are potentially more capable of solution. This research programme is pitched at the latter category in the belief that at least some improvement in current practice is feasible provided a more fundamental level of understanding of the relevant (underlying) mechanisms can be achieved. Professor E.C. Zeeman of Warwick University confirms this view with the comment, made to the writer in conversation, that "explanation should reduce the arbitrariness of description". It is only through attainment of this 'explanation' level of understanding that meaningful strategic action becomes possible. Primarily our aim here is to explain and, if possible, predict how channels of· distribution react when subjected to the forces of· change, and more specifically, change in the form of innovation A review of the literature pertinent to innovation reveals some disturbing knowledge gaps. In particular, there appears to be a general ignorance of the possible consequences of innovation, and a corresponding lack of any concerted attempt to suggest how innovation (and its consequences) may be managed in an interorganizational context. Similarly, a state-of-the-art review of the distribution channels literature leads us to conclude that, like so much of the_ general marketing literature, it is predominantly descriptive in nature. Many of the issues are developed in piecemeal fashion and hence there is no generally applicable conceptualization. Given these problems,· any attempt at predicting the effects of innovation on channel behaviour patterns is premature and bound to fail. In order to even approach our original objective therefore, it firstly becomes necessary to attempt development of a new conceptual scaffolding with 'explanation' and 'predictive' capabilities. to do this we chose to search well outside the accepted boundaries of management science literature, seeking concepts from a wide range of disciplines and inter-disciplines, building the bridges between these and observed behaviour, and using systems theory as the core around which to develop a model with more general applicability. Our research orientation is therefore predominantly theoretical but, nevertheless has substantial practical relevance. Two actual cases of significant recent innovations in the UK food/ grocery industry are used as vehicles to partially test the model, and the analysis is extended into the predictive dimension using changes delineated by a Delphi futures forecast. The intention is to use the model to anticipate (or predict) what systemic effects can be expected subsequent to the introduction of innovation. The emphasis throughout is on assessing the implications of such changes using the language and concepts -central to our model. Because the external environment is such a key influential in any 'open system' situation, considerable attention is paid to developing this aspect. Since. we are concerned with finding a new way of viewing distribution channel systems, we have adopted a macro orientation throughout" in the belief that detailed refinements can be undertaken by future researchers working within the framework established here. As such soundness of the overall logic scheme is regarded as critical, and certainly of more fundamental importance than any requirement to measure .,, individual parameters. The value of such a broad orientation should overshadow any imperfections in detail which will almost certainly emerge. Generally, the model (and its component parameters) look promising, and our findings tend to indicate that it is no longer necessary to dilute the true complexity of distribution channel systems in order to achieve some understanding of what is happening within. It is now possible to evaluate in a conceptual sense, the effects of innovation on a channel system using stability criteria, and further, to assess the viability of such innovation in terms of Ashby's 'variety' principle.